Project-Based STEAM Learning Model in Science Education to Enhance Elementary School Students’ Creative Thinking Skills - Muhammad Amran; Muhammad Irfan; Ainun Najib Alfatih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
The low creative thinking ability of elementary school students remains a problem in science learning. In addition, the learning model used has not fully encouraged the integration of 21st-century skills such as creativity and problem-solving. This study aims to analyze the STEAM-based Project-Based Learning (STEAM-PjBL) learning model to improve students' creative thinking abilities. This type of research is Research and Development (R&D) with the ADDIE development design. The research subjects consisted of 45 fifth-grade students. Data collection was carried out through validation sheets from material experts and model experts, teacher and student response questionnaires, and creative thinking ability tests through pretests and posttests. Data analysis used descriptive and inferential methods, including paired samples t-tests. The results of the study indicate that the developed STEAM-PjBL model is in the very valid category, received very positive responses from teachers and students, and has proven effective in improving students' creative thinking abilities. Thus, this learning model is suitable for use in science learning in elementary schools. The implication of this research is to provide an alternative, innovative learning model that teachers can apply to optimize the development of student creativity.